Психолінгвальні аспекти перекладу словника LIWC - Засєкін, Сергій Васильович; Zasiekin, Serhii; Безуглова, Наталія; Bezuglova, Nataliia; Гапон, Анастасія; Hapon, Anastasiia; Матюшенко, Владислав; Matiushenko, Vladyslav; Подольська, Ольга; Podolska, Olha; Зубчук, Дар’я; Zubchuk, Darya (My University, 2018)
Recent developments in computerized linguistic and psychological research tools have heightened the need for broadening not only their areas of use, but also their applied languages. Therefore, there is an urgent need to address the translation problems caused by different target culture-bound issues. Existing research in the domain of translation studies recognises the critical role played by translating transformations as psycholinguistic logical operations performed in the translator’s mind. This paper explores the ways in which selected original Linguistic Inquiry and Word Count (LIWC) 2015 (Pennebaker et al., 2015) dictionary items can be reproduced in Ukrainian with due account of their semantic, pragmatic, and cultural load. The most obvious finding to emerge from this study is that the translator should apply a set of lexical translation transformations including differerentiation, concretization, generalization of word meaning along with transсoding, explication, and calquing. Some linguistic items, e.g. from the category of ‘Leisure’, ‘Netspeak’ were not translated at all, i.e. retained their original form, due to their shared use today both by speakers of English and Ukrainian. Further research should be undertaken to investigate methods of reproducing LIWC vocabulary in other languages. Останні досягнення в галузі комп’ютерних лінгвістичних та психологічних інструментів дослідження актуалізують не лише потребу поширення сфер їхнього застосування, а й застосування з носіями різних мов. Тому актуальним видається вивчення особливостей перекладу на основі з’ясування культурних відмінностей. Дослідження сьогодення в галузі перекладознавства визнають критичну роль, що її відіграють перекладацькі трансформації як психолінгвальні логічні операції, які тривають у голові перекладача. Ця розвідка вивчає шляхи адекватного відтворення українською мовою вибраних слів зі словника програми Linguistic Inquiry and Word Count (LIWC) 2015 (Pennebaker et al., 2015) на основі встановлення їхніх семантичних, прагаматичних та культурних аспектів значення. Найголовнішим висновком дослідження є те, що перекладачеві під час роботи слід удаватися до застосування низки перекладацьких трансформацій, як-от: диференціація, конкретизація, генералізація значення слова, а також транскодування, експлікація, калькування. Деякі мовні одниці, наприклад, із категорії ‘Leisure’, ‘Netspeak’ не перекладалися взагалі, зберігаючи їхню оригінальну англомовну форму, позаяк сьогодні носії англійської та української спільно вживають таку лексику в своєму мовленні. Перспективним видається дослідження способів перекладу словника LIWC на базі інших мов.
Psycholinguistic Aspects of Translating LIWC Dictionary
Keywords: Linguistic Inquiry and Word Count (LIWC); перекладацькі трансформації; вихідна мова; цільова мова; translation transformations; source language; target language